Positive electrode active material and manufacturing method for the same, positive electrode including the same, and lithium secondary battery

JP2025031700AActive Publication Date: 2025-03-07SAMSUNG SDI CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024144046
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-08-24
Filing Date
2024-08-26
Publication Date
2025-03-07
Estimated Expiration
2044-08-26

AI Technical Summary

Benefits of technology

【0009】 本発明の一実施形態による正極活物質は、生産価格を最小化し、かつ、容量を極大化したもので、長寿命特性が確保され、高電圧での特性および高温特性が改善される。前記正極活物質を適用したリチウム二次電池は、高電圧駆動条件でも高い初期充放電容量および効率を示すことができ、長寿命特性を実現することができ、高電圧および高温駆動によるガスの発生問題を効果的に抑制することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025031700000001_ABST
    Figure 2025031700000001_ABST
Patent Text Reader

Abstract

To provide a positive electrode active material containing lithium nickel manganese composite oxide, in which the economic efficiency, high capacity, and long life are secured and the high-voltage characteristic and the high-temperature characteristic are improved, a manufacturing method for the positive electrode active material, a positive electrode including the positive electrode active material, and a lithium secondary battery.SOLUTION: A positive electrode active material includes a core particle containing layered lithium nickel manganese composite oxide, a first coating layer existing on a surface of the core particle and containing Al, and a second coating layer existing on the first coating layer and containing Co. A manufacturing method for the positive electrode active material, a positive electrode including the positive electrode active material, and a lithium secondary battery are also provided.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a positive electrode active material, a method for producing the same, a positive electrode containing the same, and a lithium secondary battery. [Background technology]

[0002] Lithium secondary batteries, which have high energy density and are easy to carry, are mainly used as the driving power source for mobile information terminals such as mobile phones, laptops, and smartphones. Recently, active research has been conducted on using high-energy-density lithium secondary batteries as driving power sources or power storage sources for hybrid and electric vehicles.

[0003] In order to realize lithium secondary batteries that meet these applications, various positive electrode active materials have been studied. Among them, lithium nickel oxide, lithium nickel manganese cobalt composite oxide, lithium nickel cobalt aluminum composite oxide, lithium cobalt oxide, etc. are mainly used as positive electrode active materials. However, in recent years, while the demand for large-sized, high-capacity, or high-energy density lithium secondary batteries has rapidly increased, the supply of positive electrode active materials containing the rare metal cobalt is expected to be extremely short. In other words, since cobalt is expensive and there are not many remaining reserves, it is necessary to develop positive electrode active materials that do not contain cobalt or have a reduced cobalt content. Summary of the Invention [Problem to be solved by the invention]

[0004] The present invention provides a positive electrode active material containing a lithium nickel-manganese composite oxide, which is economical, has high capacity, and has long life characteristics, and has improved high voltage characteristics and high temperature characteristics, a method for producing the same, and a positive electrode and a lithium secondary battery containing the same. [Means for solving the problem]

[0005] In one embodiment of the present invention, a positive electrode active material is provided, comprising: a core particle containing a layered lithium nickel-manganese composite oxide; a first coating layer located on the surface of the core particle and containing Al; and a second coating layer located on the first coating layer and containing Co.

[0006] In another embodiment of the present invention, there is provided a method for producing a positive electrode active material, comprising: mixing a layered nickel-manganese composite hydroxide and a lithium raw material; performing a first heat treatment to obtain a layered lithium nickel-manganese composite oxide; introducing an Al raw material into an aqueous solvent; introducing and mixing the lithium nickel-manganese composite oxide; introducing and mixing a Co raw material; drying the mixture; and performing a second heat treatment.

[0007] In yet another embodiment of the present invention, a positive electrode is provided, comprising a positive electrode current collector and a positive electrode active material layer located on the positive electrode current collector, the positive electrode active material layer comprising the positive electrode active material described above.

[0008] In yet another embodiment of the present invention, there is provided a lithium secondary battery comprising the positive electrode, the negative electrode, and an electrolyte. Effect of the Invention

[0009] The positive electrode active material according to an embodiment of the present invention minimizes production costs and maximizes capacity, while ensuring long life characteristics and improving high voltage and high temperature characteristics. A lithium secondary battery using the positive electrode active material can exhibit high initial charge / discharge capacity and efficiency even under high voltage driving conditions, realize long life characteristics, and effectively suppress gas generation problems caused by high voltage and high temperature driving. [Brief description of the drawings]

[0010] [Figure 1] 1 is a cross-sectional view illustrating a lithium secondary battery according to an embodiment. [Diagram 2] 1 is a cross-sectional view illustrating a lithium secondary battery according to an embodiment. [Diagram 3]1 is a cross-sectional view illustrating a lithium secondary battery according to an embodiment. [Figure 4] 1 is a cross-sectional view illustrating a lithium secondary battery according to an embodiment. [Diagram 5] 1 is a SEM image of the positive electrode active material of Example 1. [Figure 6] This is an image in which the Al element is highlighted in Figure 5 by SEM-EDS analysis. [Figure 7] This is an image in which the Co element is highlighted in Figure 5 by SEM-EDS analysis. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention is not limited to the embodiments described herein, but may be embodied in various different forms.

[0012] The terms used herein are merely used to describe exemplary embodiments and are not intended to limit the present invention. A singular expression includes a plural expression unless otherwise clearly indicated in the context.

[0013] As used herein, "combinations thereof" refers to mixtures, laminates, composites, copolymers, alloys, blends, reaction products, and the like of compositions.

[0014] It should be understood that the terms "including," "comprising," or "having" are intended to specify the presence of embodied features, numerals, steps, components, or combinations thereof, but do not preclude the presence or additional possibility of one or more other features, numerals, steps, components, or combinations thereof.

[0015] In the drawings, the thickness of the various layers and regions is exaggerated for clarity, and similar parts are designated by the same reference numerals throughout the specification. When a part such as a layer, film, region, plate, etc. is said to be "on" or "on" another part, this includes not only the case where it is "directly on" the other part, but also the case where there is another part between them. Conversely, when a part is said to be "directly on" another part, it means that there is no other part between them.

[0016] Further, the term "layer" as used herein includes not only a shape formed on the entire surface when observed in a plan view, but also a shape formed on a portion of the surface.

[0017] The average particle size can be measured by a method well known to those skilled in the art, for example, by using a particle size analyzer or by using a transmission electron microscope or a scanning electron microscope image. Alternatively, it can be measured using a dynamic light scattering method, and data analysis can be performed to count the number of particles for each particle size range, and the average particle size can be calculated from this. Unless otherwise defined, the average particle size is the diameter (D 50 In addition, unless otherwise defined, the average particle size is the diameter (D) of the particle that occupies 50% of the cumulative volume in the particle size distribution obtained by measuring the size (diameter or major axis length) of 20 or more particles randomly selected from a scanning electron microscope image. 50 ) may be taken as the average particle size.

[0018] As used herein, "or" is not to be construed in an exclusive sense, e.g., "A or B" is to be construed as including A, B, A+B, etc.

[0019] The term "metal" is interpreted as including general metals, transition metals, and metalloids (semimetals).

[0020] positive electrode active material In one embodiment of the present invention, a positive electrode active material is provided, comprising: a core particle containing a layered lithium nickel-manganese composite oxide; a first coating layer located on the surface of the core particle and containing Al; and a second coating layer located on the first coating layer and containing Co.

[0021] In recent years, the price of cobalt, a rare metal, has soared, and there is a demand for the development of positive electrode active materials that do not contain cobalt or that have a reduced content of cobalt. Among them, positive electrode active materials with an olivine crystal structure such as lithium iron phosphate (LFP), lithium manganese phosphate (LMP), and lithium manganese iron phosphate (LMFP), or a spinel crystal structure such as lithium manganese oxide (LMO), have limitations in achieving high capacity due to the small amount of lithium that can be utilized within the structure. Layered nickel-manganese positive electrode active materials have excellent capacity and efficiency characteristics because they can increase the amount of lithium within the structure, making them suitable as materials for high-capacity batteries. However, the removal of cobalt, which plays a key role in the layered structure, reduces structural stability, increases resistance, and makes it difficult to ensure long life characteristics. In addition, the removal of cobalt accelerates side reactions between the positive electrode active material and the electrolyte under high voltage and high temperature conditions, increasing the amount of gas generated and reducing life characteristics.

[0022] In one embodiment, a first coating layer and a second coating layer are introduced on the surface of a core particle containing a layered lithium nickel-manganese composite oxide to provide a cathode active material that maximizes capacity and efficiency, reduces gas generation even under high voltage and high temperature conditions, and achieves long life characteristics.

[0023] Core Particles The core particle includes a lithium nickel-manganese composite oxide. The nickel content is 60 mol% relative to 100 mol% of the total metals excluding lithium in the lithium nickel-manganese composite oxide, and may be, for example, 60 mol% to 80 mol%, 65 mol% to 80 mol%, 70 mol% to 80 mol%, 60 mol% to 79 mol%, 60 mol% to 78 mol%, or 60 mol% to 75 mol%, etc. When the nickel content satisfies the above range, a high capacity can be achieved, and structural safety can be improved even if the cobalt content is reduced.

[0024] The manganese content is, for example, 10 mol % or more relative to 100 mol % of all metals excluding lithium in the lithium nickel-manganese composite oxide, and can be, for example, 10 mol % to 40 mol %, 15 mol % to 35 mol %, 15 mol % to 30 mol %, 20 mol % to 30 mol %, etc. When the manganese content satisfies the above range, the positive electrode active material can achieve high capacity while improving structural stability.

[0025] The lithium nickel-manganese composite oxide may be, for example, a lithium nickel-manganese-aluminum composite oxide further containing aluminum in addition to nickel and manganese. When the composite oxide contains aluminum, it is advantageous to maintain a stable layered structure even if the cobalt element is excluded from the structure. The content of aluminum relative to 100 mol% of the lithium nickel-manganese-aluminum composite oxide may be 0.1 mol% or more, 0.5 mol% or more, or 1 mol% or more, for example, 1 mol% to 3 mol%, 1 mol% to 2.5 mol%, 1 mol% to 2 mol%, or 1.5 mol% to 2.5 mol%. When the content of aluminum satisfies the above range, a stable layered structure can be maintained even if cobalt is excluded, and the problem of the structure collapsing due to charging and discharging can be suppressed, and the long life characteristics of the positive electrode active material can be realized.

[0026] According to one embodiment, the aluminum concentration in the core particle may be uniform. That is, the aluminum concentration in the core particle may have a gradient from the center to the surface, or the aluminum concentration in the core particle may not be higher or lower than the inside, and the aluminum in the core particle may be uniformly dispersed. This may be a structure obtained by synthesizing a composite oxide using nickel-manganese-aluminum hydroxide as a precursor by using an aluminum raw material in the preparation of a precursor without further doping aluminum in the synthesis process of the core particle. The core particle may be in the form of a secondary particle in which a plurality of primary particles are aggregated, and the aluminum content in the primary particle may be similar or the same regardless of the position of the primary particle. That is, when a primary particle is selected from an arbitrary position in the cross section of the secondary particle and the aluminum content in the inside, not the interface of the primary particle, is measured, the aluminum content can be expressed as the same / similar / uniform regardless of the position of the primary particle, that is, whether the primary particle is close to the center or the surface of the secondary particle. In such a structure, even if cobalt is absent or present in only a very small amount, a stable layered structure can be maintained, no aluminum by-products or aluminum agglomerates are generated, and the capacity, efficiency, and life characteristics of the positive electrode active material can be improved simultaneously.

[0027] The lithium nickel-manganese composite oxide is specifically represented by the following chemical formula 1. [Chemical formula 1] Li a1 Ni x1 Mn y1 Al z1 M 1 w1 O 2-b1 X b1

[0028] In Chemical Formula 1, 0.9≦a1≦1.8, 0.6≦x1≦0.8, 0.1≦y1≦0.4, 0≦z1≦0.03, 0≦w1≦0.3, 0.9≦x1+y1+z1+w1≦1.1, and 0≦b1≦0.1; M 1is one or more elements selected from B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y, and Zr, and X is one or more elements selected from F, P, and S.

[0029] In Chemical Formula 1, 0.9 ≤ a1 ≤ 1.5, or 0.9 ≤ a1 ≤ 1.2 may hold. Further, Chemical Formula 1 contains aluminum, and in this case, 0.6 ≤ x1 ≤ 0.8, 0.1 ≤ y1 ≤ 0.39, 0.01 ≤ z1 ≤ 0.03, and 0 ≤ w1 ≤ 0.29 can be satisfied. For example, 0.6 ≤ x1 ≤ 0.8, 0.1 ≤ y1 ≤ 0.39, 0.01 < z1 ≤ 0.03, and 0 ≤ w1 ≤ 0.29 can be satisfied.

[0030] In Chemical Formula 1, for example, 0.6 ≤ x1 ≤ 0.79, 0.6 ≤ x1 ≤ 0.78, 0.6 ≤ x1 ≤ 0.75, 0.65 ≤ x1 ≤ 0.8, or 0.7 ≤ x1 ≤ 0.79, 0.1 ≤ y1 ≤ 0.35, 0.1 ≤ y1 ≤ 0.30, 0.1 ≤ y1 ≤ 0.29, 0.15 ≤ y1 ≤ 0.39, or 0.2 ≤ y1 ≤ 0.3, 0.01 ≤ z1 ≤ 0.025, 0.01 < z1 ≤ 0.02, or 0.01 < z1 ≤ 0.019, 0 ≤ w1 ≤ 0.28, 0 ≤ w1 ≤ 0.27, 0 ≤ w1 ≤ 0.26, 0 ≤ w1 ≤ 0.25, 0 ≤ w1 ≤ 0.24, 0 ≤ w1 ≤ 0.23, 0 ≤ w1 ≤ 0.22, 0 ≤ w1 ≤ 0.21, 0 ≤ w1 ≤ 0.2, 0 ≤ w1 ≤ 0.15, 0 ≤ w1 ≤ 0.1, or 0 ≤ w1 ≤ 0.09, etc. may hold.

[0031] The lithium nickel-manganese composite oxide may be a cobalt-free compound that does not contain cobalt or contains a very small amount of cobalt. For example, in the lithium nickel-manganese composite oxide, the content of cobalt relative to 100 mol% of the total metal excluding lithium may be 0 mol% to 0.01 mol%.

[0032] The core particle may be in the form of a secondary particle formed by agglomeration of a plurality of primary particles. The secondary particles may be spherical, ellipsoidal, polyhedral, or irregular in shape, while the primary particles may be spherical, ellipsoidal, plate-like, or a combination thereof.

[0033] The core particles are susceptible to chemical attack by components in the electrolyte when the battery is operated under high voltage or high temperature conditions, and many side reactions with the electrolyte may occur, which may result in a large amount of gas generation and reduced battery life and safety. However, such problems can be solved by introducing a coating layer according to one embodiment described below.

[0034] First Coating Layer The Al content in the first coating layer is 0.1 mol% to 2 mol% relative to 100 mol% of the total metals excluding lithium in the positive electrode active material, and may be, for example, 0.2 mol% to 1.9 mol%, 0.3 mol% to 1.8 mol%, 0.5 mol% to 1.5 mol%, or 0.8 mol% to 1.3 mol%. This means only the content of aluminum contained in the first coating layer, apart from the aluminum contained in the core particles. The aluminum content in the first coating layer can be measured, for example, by SEM-EDS analysis of the surface or cross section of the positive electrode active material. When the aluminum content in the first coating layer satisfies the above range, it is possible to form a coating layer with a uniform and thin thickness, the resistance of the positive electrode active material does not increase, side reactions with the electrolyte are effectively suppressed, and the life characteristics of the lithium secondary battery under high voltage and high temperature conditions can be improved. For example, if the aluminum content of the first coating layer is too high, a uniform coating layer may not be formed or the resistance may increase, resulting in reduced charge / discharge efficiency and reduced life characteristics. Conversely, if the aluminum content of the first coating layer is too low, a coating layer of appropriate thickness may not be formed, resulting in reduced effect of suppressing side reactions with the electrolyte.

[0035] The first coating layer may be in the form of a film that continuously surrounds the surface of the core particle, for example, in the form of a shell that surrounds the entire surface of the core particle. This is distinguished from a structure in which only a portion of the surface of the core particle is partially coated. According to one embodiment, the first coating layer may be formed in a form that entirely surrounds the surface of the core particle, but with a very thin and uniform thickness, so that the positive electrode active material does not increase in resistance or decrease in capacity, improves structural stability, effectively suppresses side reactions with the electrolyte, reduces the amount of gas generation under high voltage and high temperature conditions, and achieves long life characteristics.

[0036] The thickness of the first coating layer is 5 nm to 40 nm, and may be, for example, 5 nm to 30 nm, or 5 nm to 20 nm. When the first coating layer satisfies the above thickness range, the coating does not increase resistance or decrease capacity, and the structural stability of the positive electrode active material is improved, and side reactions with the electrolyte can be effectively suppressed. The thickness of the coating layer can be measured, for example, by SEM, TEM, TOF-SIMS, XPS, or EDS analysis, and the thickness range of the coating layer can be measured by TEM-EDS line profile.

[0037] The first coating layer may be thicker than the second coating layer described below.

[0038] The first coating layer is characterized by being thin and uniform in thickness, at the level of tens to hundreds of nanometers. For example, the deviation in thickness of the first coating layer within one positive electrode active material particle may be 20% or less, 18% or less, or 15% or less. Here, the deviation in thickness of the coating layer refers to the content of the coating layer within one positive electrode active material particle. The deviation in thickness of the coating layer means, for example, that the thickness of 10 or more points is measured in an electron microscope image of a cross section of one positive electrode active material particle, the arithmetic average is calculated, and the absolute value of the difference between one data and the arithmetic average value is divided by the arithmetic average value and multiplied by 100. The deviation or standard deviation of the thickness of the first coating layer satisfies the above range, which means that a coating layer of uniform thickness is well formed in the form of a film on the surface of the positive electrode active material particle, thereby improving the structural stability of the positive electrode active material, effectively suppressing side reactions with the electrolyte, and minimizing the increase in resistance and the decrease in capacity due to the coating.

[0039] The first coating layer can include, for example, aluminum oxide, lithium-aluminum oxide, or a combination thereof. The first coating layer can have a layered structure. That is, the compound included in the first coating layer can have a layered structure.

[0040] In addition to aluminum, the first coating layer may further include nickel, manganese, or a combination thereof.

[0041] Second Coating Layer The Co content in the second coating layer is 0.01 mol% to 1 mol% relative to 100 mol% of the total metals excluding lithium in the positive electrode active material, and may be, for example, 0.01 mol% to 0.9 mol%, 0.01 mol% to 0.7 mol%, 0.05 mol% to 0.5 mol%, or 0.1 mol% to 0.4 mol%. The Co content in the second coating layer can be measured, for example, by SEM-EDS analysis of the surface or cross section of the positive electrode active material. When the Co content in the second coating layer satisfies the above range, it is possible to form a coating layer with a uniform and thin thickness, the resistance of the positive electrode active material does not increase, side reactions with the electrolyte are effectively suppressed, and the life characteristics of the lithium secondary battery under high voltage and high temperature conditions can be improved. For example, if the Co content of the second coating layer is too high, a uniform coating layer may not be formed or the resistance may increase, resulting in reduced charge / discharge efficiency and reduced life characteristics. Conversely, if the Co content of the second coating layer is too low, a coating layer of appropriate thickness may not be formed, the effect of suppressing side reactions with the electrolyte may be reduced, or the charge / discharge efficiency and high-temperature life characteristics may be reduced.

[0042] The second coating layer may be in the form of a film or shell that continuously surrounds the surface of the first coating layer. According to one embodiment, the second coating layer may be formed in a form that entirely surrounds the outermost surface of the positive electrode active material, and may be formed to a very thin and uniform thickness, so that the positive electrode active material does not increase in resistance or decrease in capacity, improves structural stability, effectively suppresses side reactions with the electrolyte, reduces gas generation under high voltage and high temperature conditions, and achieves long life characteristics.

[0043] The thickness of the second coating layer is 10 nm or less, and may be, for example, 0.1 nm to 10 nm, 0.5 nm to 9 nm, 1 nm to 7 nm, or 1 nm to 5 nm. When the second coating layer satisfies the above thickness range, the coating does not increase the resistance or decrease the capacity, but improves the structural stability of the positive electrode active material and effectively suppresses side reactions with the electrolyte. The thickness of the coating layer may be measured, for example, by SEM, TEM, TOF-SIMS, XPS, or EDS analysis, and the thickness range of the coating layer may be measured by TEM-EDS line profile.

[0044] The second coating layer is characterized by being thin, at the level of several nanometers, and having a uniform thickness. For example, the deviation in thickness of the second coating layer within one positive electrode active material particle may be 20% or less, 18% or less, or 15% or less. Here, the deviation in thickness of the coating layer refers to the thickness of the coating layer within one positive electrode active material particle. The deviation in thickness of the coating layer means, for example, that the thickness of 10 or more points is measured in an electron microscope image of a cross section of one positive electrode active material particle, the arithmetic average is calculated, and the absolute value of the difference between one data and the arithmetic average value is divided by the arithmetic average value and multiplied by 100. The deviation or standard deviation of the thickness of the second coating layer satisfies the above range, which means that a coating layer of uniform thickness is well formed in the form of a film on the outermost surface of the positive electrode active material particle, thereby improving the structural stability of the positive electrode active material, effectively suppressing side reactions with the electrolyte, and minimizing the increase in resistance and the decrease in capacity due to the coating.

[0045] The second coating layer may further include Al in addition to Co. The second coating layer may include, for example, cobalt oxide, lithium-cobalt oxide, aluminum-cobalt oxide, lithium-aluminum-cobalt oxide, or a combination thereof. The second coating layer may have a layered structure. The core, the first coating layer, and the second coating layer all have a layered crystal structure, which can further promote the insertion and desorption of lithium.

[0046] Meanwhile, the first coating layer may be thicker than the second coating layer. For example, the ratio of the thickness of the second coating layer to the thickness of the first coating layer may be less than 0.5, for example, 0.4 or less, or 0.3 or less. When the thicknesses of the first coating layer and the second coating layer satisfy such a relationship, the coating does not increase resistance or decrease capacity, but improves the structural stability of the positive electrode active material, and effectively suppresses side reactions with the electrolyte to improve high voltage characteristics and high temperature characteristics.

[0047] The Al content of the first coating layer may be greater than the Co content of the second coating layer. Here, the content refers to the molar content, and refers to the molar content relative to 100 mol% of metals excluding lithium in the positive electrode active material. For example, the ratio of the Co content of the second coating layer to the Al content of the first coating layer may be less than 0.5, for example, 0.4 or less, 0.3 or less. When the Al content of the first coating layer and the Co content of the second coating layer satisfy this relationship, the coating does not increase resistance or decrease capacity, but improves the structural stability of the positive electrode active material, and effectively suppresses side reactions with the electrolyte to improve high voltage characteristics and high temperature characteristics.

[0048] Grain boundary coating part Meanwhile, in the process of forming the first coating layer, aluminum may be diffused into the core particles. Thus, the positive electrode active material according to an embodiment may further include a grain boundary coating portion containing aluminum and located on the surface of the primary particle inside the secondary particle. Here, the secondary particle refers to the core particle, and the inside of the secondary particle may refer to the entire inside except for the surface of the secondary particle, or may refer to a region from the surface of the secondary particle to about 60% of the radius in the direction toward the center of the secondary particle. The grain boundary coating portion is a concept distinct from the coating layer on the surface of the core particle, and refers to a coating portion formed on the surface of the primary particle located inside the core particle. The presence of the grain boundary coating portion may be confirmed by SEM-EDS analysis of the cross section of the positive electrode active material. The formation of the aluminum grain boundary coating portion further stabilizes the structure of the positive electrode active material, improving the life characteristics.

[0049] The aluminum content in the grain boundary coating portion is not particularly limited, and as an example, the aluminum content in the grain boundary coating portion may be less than the aluminum content in the coating layer.

[0050] In addition, the grain boundary coating portion may further include nickel, manganese, yttrium, or a combination thereof in addition to aluminum.

[0051] The average particle size (D 50 The average particle size is determined by measuring the size (diameter or major axis length) of 20 or more random particles in a scanning electron microscope image of the positive electrode active material to obtain a particle size distribution, and calculating the diameter (D) of the particle that occupies 50% of the cumulative volume in the particle size distribution. 50 When the average particle size of the positive electrode active material satisfies the above range, high capacity and long life can be achieved, and it is advantageous to form the coating layer according to an embodiment.

[0052] In the positive electrode active material according to an embodiment, the content of cobalt may be, for example, 0.01 mol % or less, 0.005 mol % or less, 0.001 mol % or less, for example, 0 mol % to 0.01 mol %, relative to 100 mol % of all metals excluding lithium. The positive electrode active material according to an embodiment may be, for example, a cobalt-free positive electrode active material.

[0053] In addition, the positive electrode active material according to an embodiment may be characterized in that it does not contain sodium. Although sodium ions can be generally used in a process for manufacturing a positive electrode active material, according to a manufacturing method described below, it is possible to form core particles with a stable structure and a coating layer with a uniform thickness without using sodium ions.

[0054] Method for producing positive electrode active material In one embodiment, a method for producing a positive electrode active material is provided, which includes mixing a layered nickel-manganese composite hydroxide and a lithium raw material, performing a first heat treatment to obtain a lithium nickel-manganese composite oxide, adding an Al raw material to an aqueous solvent, adding and mixing the lithium nickel-manganese composite oxide, adding and mixing a Co raw material, drying the mixture, and performing a second heat treatment. The above-mentioned positive electrode active material can be produced by the above method.

[0055] The layered nickel-manganese composite hydroxide is a precursor of core particles, and may be in the form of secondary particles formed by agglomeration of a plurality of primary particles, and may contain no cobalt or a very small amount of cobalt, for example, a cobalt-free nickel-manganese composite hydroxide. The nickel-manganese-aluminum composite hydroxide may be prepared by a conventional coprecipitation method.

[0056] In the layered nickel-manganese composite hydroxide, the nickel content is 60 mol% or more relative to 100 mol% of the total metal, and can be, for example, 60 mol% to 80 mol%, 65 mol% to 80 mol%, 70 mol% to 80 mol%, 60 mol% to 79 mol%, 60 mol% to 78 mol%, or 60 mol% to 75 mol%, etc. When the nickel content satisfies the above range, a high capacity can be achieved, and structural safety can be improved even if the cobalt content is reduced.

[0057] The manganese content in the layered nickel-manganese composite hydroxide is 10 mol% or more relative to 100 mol% of the total metal, and can be, for example, 10 mol% to 40 mol%, 15 mol% to 39 mol%, 15 mol% to 35 mol%, 15 mol% to 30 mol%, or 20 mol% to 30%, etc.

[0058] In addition, when the layered nickel-manganese composite hydroxide further contains aluminum, the aluminum content is 0.1 mol% or more, 0.5 mol% or more, or 1 mol% or more, for example, 1 mol% to 3 mol%, 1 mol% to 2.5 mol%, 1 mol% to 2 mol%, or 1 mol% to 1.9 mol%, based on 100 mol% of the total metal. When the manganese and aluminum contents in the composite hydroxide are within the above ranges, high capacity can be achieved, and the structural safety of the positive electrode active material can be improved, and the production cost can be reduced to improve the economic efficiency.

[0059] In one embodiment, the method for producing a positive electrode active material uses an aluminum raw material when producing a precursor without further doping aluminum during the production of core particles, and can use a nickel-manganese-aluminum composite hydroxide in which aluminum is uniformly dispersed within the structure as a precursor. By using such a precursor, a positive electrode active material that does not contain cobalt and stably maintains a layered structure even after repeated charging and discharging can be produced, and aluminum by-products and aluminum aggregates are not formed, thereby improving the capacity, efficiency characteristics, and life characteristics of the positive electrode active material.

[0060] In the layered nickel-manganese composite hydroxide, the cobalt content may be 0.01 mol% or less, 0.005 mol% or less, or 0.001 mol% or less, based on 100 mol% of the total metal. Such a nickel-manganese composite hydroxide can avoid an increase in unit price due to cobalt, and is economical, and can maximize capacity and improve structural stability.

[0061] An example of a layered nickel-manganese composite hydroxide is represented by the following chemical formula 2. [Chemical formula 2] Ni x2 Mn y2 Al z2 M 2 w2 (OH)2

[0062] In the chemical formula 2, 0.6≦x2≦0.8, 0.1≦y2≦0.4, 0≦z2≦0.03, 0≦w2≦0.3, and 0.9≦x2+y2+z2+w2≦1.1; M 2 is one or more elements selected from B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y, and Zr.

[0063] In Chemical Formula 2, for example, 6≦x2≦0.8, 0.1≦y2≦0.39, 0.01≦z2≦0.03, and 0≦w2≦0.29.

[0064] The layered nickel-manganese composite hydroxide is in the form of particles, and the average particle size (D 50 ) can be 1 μm to 25 μm, 5 μm to 20 μm, 10 μm to 20 μm, 11 μm to 18 μm, or 12 μm to 15 μm.

[0065] The layered nickel-manganese composite hydroxide and the lithium raw material can be mixed in a molar ratio of 1:0.9 to 1:1.8, for example, 1:0.9 to 1:1.5 or 1:0.9 to 1:1.2. The first heat treatment can be carried out in an oxygen atmosphere, for example, at a temperature range of 750°C to 950°C, or 780°C to 900°C, or 810°C to 890°C, for 2 hours to 20 hours, or 4 hours to 12 hours. A lithium nickel-manganese composite oxide can be obtained by the heat treatment. The obtained composite oxide is substantially the same as that described for the core particles in the section on the positive electrode active material.

[0066] The layered lithium nickel-manganese composite oxide has a significantly different content of residual lithium on the particle surface from existing nickel-based oxides of other compositions, such as lithium nickel-cobalt-manganese composite oxide and lithium nickel-cobalt-aluminum composite oxide, and has many different surface properties, making it impossible to form a good coating layer with a uniform film shape using existing coating methods. In one embodiment, a method is provided for improving high voltage characteristics by forming a uniform coating layer with a very thin thickness on the surface of a lithium nickel-manganese composite oxide with a very small cobalt content and a nickel content of 60 mol% or more.

[0067] In one embodiment, an Al raw material is added to an aqueous solvent and mixed, and then a layered lithium nickel-manganese composite oxide is added and mixed to induce a first coating layer on the surface of the layered lithium nickel-manganese composite oxide particle (core particle). Next, a Co raw material is added to the mixed solution and mixed to induce a second coating layer. Then, the mixed solution is dried to remove the solvent, and a second heat treatment is performed to obtain a positive electrode active material in which an Al-containing first coating layer and a Co-containing second coating layer are sequentially formed on the surface of the core particle. This may be a continuous wet coating method.

[0068] The aqueous solvent may include distilled water, an alcohol-based solvent, or a combination thereof. The Al raw material may include, for example, aluminum nitrate, aluminum sulfate, aluminum carbonate, aluminum hydroxide, or a combination thereof. As an example, the Al raw material may include aluminum sulfate, which is advantageous in forming a first coating layer having a uniform thickness on the surface of the lithium nickel-manganese composite oxide particles.

[0069] The Al raw material is a raw material for forming the coating layer, and the Al content in the Al raw material can be designed to be 0.1 mol% to 2 mol% with respect to 100 mol% of the total metals excluding lithium in the finally obtained positive electrode active material, for example, 0.2 mol% to 1.9 mol%, 0.3 mol% to 1.8 mol%, 0.5 mol% to 1.5 mol%, or 0.8 mol% to 1.3 mol%. By designing the Al coating content within the above range, a first coating layer having a thin and uniform thickness of several tens to several hundreds of nanometers can be formed, and the amount of gas generation of the lithium secondary battery under high voltage or high temperature driving conditions can be reduced, and high capacity and long life characteristics can be improved.

[0070] The solution in which the Al raw material is added to the aqueous solvent has a pH of 1.5 to 3.5, for example, 2.0 to 3.4, 2.5 to 3.3, 2.7 to 3.3, or 2.9 to 3.2. The lithium nickel-manganese composite oxide can be added to the aqueous solvent in which the aluminum raw material is mixed and mixed for about 5 to 80 minutes, or 5 to 60 minutes, or 5 to 40 minutes. The pH of the mixed solution after stirring is 4.5 to 8.5, for example, 5.0 to 8.0, 5.5 to 7.5, or 6.0 to 7.0. When such conditions are satisfied, it is advantageous for a first coating layer of uniform thickness to be formed.

[0071] The Co raw material may include, for example, cobalt nitrate, cobalt sulfate, cobalt carbonate, cobalt hydroxide, or a combination thereof. The Co content in the Co raw material may be designed to be 0.01 mol% to 1 mol% with respect to 100 mol% of the total metals excluding lithium in the positive electrode active material, for example, 0.01 mol% to 0.9 mol%, 0.01 mol% to 0.7 mol%, 0.05 mol% to 0.5 mol%, or 0.1 mol% to 0.4 mol%. By designing the content of the Co coating within the above range, a second coating layer having a thin thickness of several nanometers and a uniform thickness can be formed, improving the performance of the lithium secondary battery under high voltage or high temperature driving conditions, and improving the high capacity and long life characteristics.

[0072] The Co raw material can be added and mixed for about 5 to 80 minutes, or 5 to 60 minutes, or 10 to 40 minutes. The pH of the final mixed solution after stirring is 4.5 to 8.5, for example, 5.0 to 8.0, 5.5 to 7.5, or 6.0 to 7.0. If such conditions are met, it is advantageous for a second coating layer of uniform thickness to be formed.

[0073] The mixed solution can be dried by removing the solvent, for example, at 40°C to 240°C, 100°C to 220°C, or 150°C to 200°C.

[0074] The second heat treatment can be carried out, for example, in an oxygen atmosphere at a temperature range of 700°C to 850°C, 750°C to 840°C, or 800°C to 830°C for 2 hours to 20 hours or 3 hours to 10 hours. The second heat treatment temperature can be lower than the first heat treatment temperature, and the second heat treatment time is preferably the same as or shorter than the first heat treatment time. By carrying out the second heat treatment under such conditions, a desired coating layer can be obtained.

[0075] positive electrode In one embodiment, the positive electrode includes a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector, the positive electrode active material layer including the positive electrode active material described above. The positive electrode active material layer may further include other types of positive electrode active materials in addition to the positive electrode active materials described above. The positive electrode active material layer may also optionally include a binder, a conductive material, or a combination thereof.

[0076] According to one embodiment, the loading level of the positive electrode active material layer is 10 mg / cm 2 ~40mg / cm 2 For example, 10 mg / cm 2 ~30mg / cm 2 or 10 mg / cm 2 ~20mg / cm 2 In addition, the density of the positive electrode active material layer in the final rolled positive electrode may be 3.3 g / cc to 3.7 g / cc, for example, 3.3 g / cc to 3.6 g / cc or 3.4 g / cc to 3.58 g / cc. When the positive electrode active material according to an embodiment is applied, it is advantageous to achieve such a loading level and positive electrode density, and a positive electrode satisfying the above-mentioned ranges of loading level and positive electrode density is suitable for realizing a lithium secondary battery with high capacity and high energy density.

[0077] binder The binder serves to make the positive electrode active material particles adhere well to each other and to make the positive electrode active material adhere well to the current collector. Representative examples of the binder include, but are not limited to, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, epoxy resin, (meth)acrylic resin, polyester resin, nylon, etc.

[0078] Conductive material The conductive material is used to impart electrical conductivity to the electrodes, and any material that does not cause chemical changes in the battery that is constructed and is electronically conductive can be used. Examples of the conductive material include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, carbon fibers, carbon nanofibers, and carbon nanotubes; metal-based materials containing copper, nickel, aluminum, silver, and the like in the form of metal powder or metal fibers; conductive polymers such as polyphenylene derivatives; and mixtures thereof.

[0079] The content of the binder and the conductive material may be 0.5% by weight to 5% by weight, respectively, relative to 100% by weight of the positive electrode active material layer.

[0080] The positive electrode current collector can be made of Al, but is not limited to this.

[0081] Lithium secondary battery In one embodiment, a lithium secondary battery is provided that includes the above-described positive electrode, negative electrode, and electrolyte. For example, the lithium secondary battery may include a positive electrode, a negative electrode, a separator disposed between the positive electrode and the negative electrode, and an electrolyte.

[0082] Lithium secondary batteries can be classified into cylindrical, square, pouch, coin, and other types according to their shapes. FIGS. 1 to 4 are schematic diagrams showing a lithium secondary battery according to an embodiment, in which FIG. 1 shows a circular battery, FIG. 2 shows a square battery, and FIGS. 3 and 4 show a pouch battery. Referring to FIGS. 1 to 4, the lithium secondary battery 100 can include an electrode assembly 40 between a positive electrode 10 and a negative electrode 20, with a separator 30 interposed therebetween, and a case 50 in which the electrode assembly 40 is housed. The positive electrode 10, the negative electrode 20, and the separator 30 may be impregnated with an electrolyte (not shown). The lithium secondary battery 100 can include a sealing member 60 that seals the case 50, as shown in FIG. 1. In addition, in FIG. 2, the lithium secondary battery 100 can include a positive electrode lead tab 11, a positive electrode terminal 12, a negative electrode lead tab 21, and a negative electrode terminal 22. As shown in FIGS. 3 and 4, the lithium secondary battery 100 may include electrode tabs 70, i.e., a positive electrode tab 71 and a negative electrode tab 72, which serve as electrical paths for conducting the current generated in the electrode assembly 40 to the outside.

[0083] The lithium secondary battery according to an embodiment may be capable of being charged at a high voltage or may be suitable for being driven at a high voltage. For example, the charging voltage of the lithium secondary battery may be 4.45 V or more, such as 4.45 V to 4.7 V, 4.45 V to 4.6 V, or 4.45 V to 4.55 V. By applying the positive electrode active material according to an embodiment, the lithium secondary battery can significantly reduce the amount of gas generated even when charged at a high voltage, and can achieve high capacity and long life characteristics.

[0084] negative electrode The negative electrode can include a current collector and a negative electrode active material layer located on the current collector, the negative electrode active material layer including a negative electrode active material and can further include a binder, a conductive material, or a combination thereof.

[0085] negative electrode active material The negative electrode active material includes a material capable of reversibly inserting / desorbing lithium ions, lithium metal, an alloy of lithium metal, a material dopable and dedopable with lithium, or a transition metal oxide.

[0086] Examples of the material capable of reversibly inserting / desorbing the lithium ions include carbon-based negative electrode active materials, which can include, for example, crystalline carbon, amorphous carbon, or a combination thereof. Examples of the crystalline carbon include graphite such as amorphous, plate-like, flaky, spherical, or fibrous natural graphite, or artificial graphite, and examples of the amorphous carbon include soft carbon or hard carbon, mesophase pitch carbide, fired coke, and the like.

[0087] As the alloy of lithium metal, an alloy of lithium and a metal selected from Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn can be used.

[0088] As the material dopable and dedopable with lithium, an Si-based negative electrode active material or an Sn-based negative electrode active material can be used. The Si-based negative electrode active material can be silicon, a silicon-carbon composite, SiOx (0 < x < 2), an Si-Q alloy (where Q is an element selected from alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements (excluding Si), Group 15 elements, Group 16 elements, transition metals, rare earth elements, and combinations thereof, for example, Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po, and combinations thereof), or a combination thereof. The Sn-based negative electrode active material can be Sn, SnO2, an Sn alloy, or a combination thereof.

[0089] The silicon-carbon composite may be a composite of silicon and amorphous carbon. The average particle size (D 50 ) may be, for example, 0.5 μm to 20 μm. According to one embodiment, the silicon-carbon composite may be in the form of silicon particles and the surfaces of the silicon particles coated with amorphous carbon. For example, it may include secondary particles (cores) formed by granulating primary silicon particles, and an amorphous carbon coating layer (shell) located on the surfaces of the secondary particles. The amorphous carbon may also be located between the primary silicon particles, for example, the primary silicon particles may be coated with amorphous carbon. The secondary particles may be present dispersed in an amorphous carbon matrix.

[0090] The silicon-carbon composite may further include crystalline carbon. For example, the silicon-carbon composite may include a core including crystalline carbon and silicon particles, and an amorphous carbon coating layer located on the surface of the core. The crystalline carbon may be artificial graphite, natural graphite, or a combination thereof. The amorphous carbon may include soft or hard carbon, mesophase pitch carbide, calcined coke, etc.

[0091] When the silicon-carbon composite contains silicon and amorphous carbon, the silicon content may be 10% to 50% by weight and the amorphous carbon content may be 50% to 90% by weight, relative to 100% by weight of the silicon-carbon composite. When the composite contains silicon, amorphous carbon and crystalline carbon, the silicon content may be 10% to 50% by weight, the crystalline carbon content may be 10% to 70% by weight, and the amorphous carbon content may be 20% to 40% by weight, relative to 100% by weight of the silicon-carbon composite.

[0092] The thickness of the amorphous carbon coating layer may be 5 nm to 100 nm. 50) can be 10 nm to 1 μm, or 10 nm to 200 nm. The silicon particles may exist alone as silicon, or in the form of a silicon alloy, or in an oxidized form. The oxidized form of silicon can be represented by SiO x (0 < x < 2). At this time, the atomic content ratio of Si:O indicating the degree of oxidation can be 99:1 to 33:67. In this specification, unless otherwise defined, the average particle size (D 50 ) means the diameter of the particle with a cumulative volume of 50% by volume in the particle size distribution.

[0093] The Si-based negative electrode active material or the Sn-based negative electrode active material can be used by mixing with a carbon-based negative electrode active material. When the Si-based negative electrode active material or the Sn-based negative electrode active material and the carbon-based negative electrode active material are used in combination, the mixing ratio can be 1:99 to 90:10 by weight.

[0094] binder The binder serves to make the negative electrode active material particles adhere well to each other and also make the negative electrode active material adhere well to the current collector. As the binder, a non-aqueous binder, an aqueous binder, a dry binder, or a combination thereof can be used.

[0095] Examples of the non-aqueous binder include polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene-propylene copolymer, polystyrene, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamideimide, polyimide, or a combination thereof.

[0096] The water-based binder may be selected from styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, (meth)acrylonitrile-butadiene rubber, (meth)acrylic rubber, butyl rubber, fluororubber, polyethylene oxide, polyvinylpyrrolidone, polyepichlorohydrin, polyphosphazene, poly(meth)acrylonitrile, ethylene propylene diene copolymer, polyvinylpyridine, chlorosulfonated polyethylene, latex, polyester resin, (meth)acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol, and combinations thereof.

[0097] When an aqueous binder is used as the negative electrode binder, a cellulose-based compound capable of imparting viscosity may be further included. As the cellulose-based compound, one or more of carboxymethylcellulose, hydroxypropylmethylcellulose, methylcellulose, or alkali metal salts thereof may be mixed and used. As the alkali metal, Na, K, or Li may be used.

[0098] The dry binder can be a fiberizable polymeric material such as polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, or combinations thereof.

[0099] Conductive material The conductive material is used to impart electrical conductivity to the electrodes, and may be any material that does not cause chemical changes in the battery and is electronically conductive. Specific examples include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, carbon fibers, carbon nanofibers, and carbon nanotubes; metal-based materials in the form of metal powder or metal fibers, including copper, nickel, aluminum, and silver; conductive polymers such as polyphenylene derivatives; and mixtures thereof.

[0100] The content of the negative electrode active material may be 95% to 99.5% by weight relative to 100% by weight of the negative electrode active material layer, and the content of the binder may be 0.5% to 5% by weight relative to 100% by weight of the negative electrode active material layer. For example, the negative electrode active material layer may contain 90% to 99% by weight of the negative electrode active material, 0.5% to 5% by weight of the binder, and 0.5% to 5% by weight of the conductive material.

[0101] Current collector The negative electrode current collector can include, for example, indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li), or alloys thereof, and can be in foil, sheet, or foam form. The thickness of the negative electrode current collector can be, for example, 1 μm to 20 μm, 5 μm to 15 μm, or 7 μm to 10 μm.

[0102] electrolyte The electrolyte for a lithium secondary battery can be, by way of example, an electrolytic solution, which can include a non-aqueous organic solvent and a lithium salt.

[0103] The non-aqueous organic solvent serves as a medium through which the ions involved in the electrochemical reactions of the battery can migrate. The non-aqueous organic solvent may be a carbonate-, ester-, ether-, ketone-, or alcohol-based solvent, an aprotic solvent, or a combination thereof.

[0104] Examples of the carbonate solvent include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), etc. Examples of the ester solvent include methyl acetate, ethyl acetate, n-propyl acetate, dimethyl acetate, methyl propionate, ethyl propionate, decanolide, mevalonolactone, valerolactone, caprolactone, etc. Examples of the ether solvent include dibutyl ether, tetraglyme, diglyme, dimethoxyethane, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, and tetrahydrofuran. Examples of the ketone solvent include cyclohexanone. Examples of the alcohol solvent include ethyl alcohol and isopropyl alcohol. Examples of the aprotic solvent include nitriles such as R-CN (R is a straight-chain, branched, or cyclic hydrocarbon group having 2 to 20 carbon atoms, and may contain a double bond, an aromatic ring, or an ether group); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane and 1,4-dioxolane; and sulfolanes.

[0105] The non-aqueous organic solvent may be used alone or in combination of two or more kinds. When using in combination of two or more kinds, the mixing ratio may be appropriately adjusted according to the desired battery performance, which is widely understood by those working in the field.

[0106] When a carbonate-based solvent is used, a cyclic carbonate and a chain carbonate can be mixed and used, and the cyclic carbonate and the chain carbonate can be mixed in a volume ratio of 1:1 to 1:9.

[0107] The non-aqueous organic solvent may further include an aromatic hydrocarbon organic solvent. For example, the carbonate solvent and the aromatic hydrocarbon organic solvent may be mixed in a volume ratio of 1:1 to 30:1.

[0108] The electrolyte may further contain a vinyl ethyl carbonate, vinylene carbonate or ethylene carbonate based compound to improve the battery life.

[0109] Representative examples of the ethylene carbonate-based compounds include fluoroethylene carbonate, difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, and cyanoethylene carbonate.

[0110] Lithium salts are substances that dissolve in organic solvents and act as a source of lithium ions in the battery to enable basic lithium secondary battery operation and facilitate the movement of lithium ions between the positive and negative electrodes. Representative examples of lithium salts include LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, LiCl, LiI, LiN(SO3C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide; LiFSI), LiC4F9SO3, LiN(C x F 2x+1 SO2)(C y F 2y+1 SO2) (x and y are integers from 1 to 20), lithium trifluoromethanesulfonate, lithium tetrafluoroethanesulfonate, lithium difluorobis(oxalato)phosphate (LiDFOB), and lithium bis(oxalato)borate (LiBOB).

[0111] The lithium salt is preferably used at a concentration within the range of 0.1 M to 2.0 M. If the lithium salt concentration is within the above range, the electrolyte has appropriate ion conductivity and viscosity, and therefore can exhibit excellent performance and allow lithium ions to migrate effectively.

[0112] Separator Depending on the type of lithium secondary battery, a separator may be present between the positive electrode and the negative electrode. As such a separator, polyethylene, polypropylene, polyvinylidene fluoride, or a multilayer film of two or more layers of these may be used, and it is of course possible to use a mixed multilayer film such as a two-layer separator of polyethylene / polypropylene, a three-layer separator of polyethylene / polypropylene / polyethylene, or a three-layer separator of polypropylene / polyethylene / polypropylene.

[0113] The separator may include a porous substrate and a coating layer including an organic material, an inorganic material, or a combination thereof located on one or both sides of the porous substrate.

[0114] The porous substrate may be a polymer membrane formed of any one polymer selected from polyolefins such as polyethylene and polypropylene, polyesters such as polyethylene terephthalate and polybutylene terephthalate, polyacetal, polyamide, polyimide, polycarbonate, polyether ketone, polyaryl ether ketone, polyetherimide, polyamide imide, polybenzimidazole, polyethersulfone, polyphenylene oxide, cyclic olefin copolymer, polyphenylene sulfide, polyethylene naphthalate, glass fiber, Teflon (registered trademark), and polytetrafluoroethylene, or a copolymer or mixture of two or more of these polymers.

[0115] The porous substrate can have a thickness of about 1 μm to 40 μm, for example, 1 μm to 30 μm, 1 μm to 20 μm, 5 μm to 15 μm, or 10 μm to 15 μm.

[0116] The organic material may include a (meth)acrylic copolymer including a first structural unit derived from (meth)acrylamide, a structural unit derived from (meth)acrylic acid or a (meth)acrylate, and a second structural unit including at least one of a structural unit derived from (meth)acrylamidosulfonic acid or a salt thereof.

[0117] The inorganic material may include, but is not limited to, inorganic particles selected from Al2O3, SiO2, TiO2, SnO2, CeO2, MgO, NiO, CaO, GaO, ZnO, ZrO2, Y2O3, SrTiO3, BaTiO3, Mg(OH)2, boehmite, and combinations thereof. The average particle size (D 50 ) may be 1 nm to 2000 nm, for example, 100 nm to 1000 nm, or 100 nm to 700 nm.

[0118] The organic material and the inorganic material may be mixed in one coating layer, or may be stacked in a coating layer including an organic material and a coating layer including an inorganic material.

[0119] The thickness of each of the coating layers may be from 0.5 μm to 20 μm, for example, from 1 μm to 10 μm, or from 1 μm to 5 μm.

[0120] Examples of the present invention and comparative examples are described below. The following examples are merely illustrative of the present invention, and the present invention is not limited to the following examples.

[0121] Example 1 1. Manufacturing of positive electrode active material Ni 0.75 Mn 0.23 Al 0.02 (OH)2 and LiOH were mixed in a 1:1 molar ratio and subjected to a first heat treatment at 850°C for 8 hours in an oxygen atmosphere to obtain a compound with the composition LiNi 0.75 Mn 0.23 Al 0.02O2 and the average particle size (D 50 A composite oxide in the form of secondary particles having a particle size of about 14 μm was produced.

[0122] After mixing aluminum sulfate with distilled water solvent, the prepared composite oxide was added and mixed for about 20 to 60 minutes. At this time, the aluminum content in the aluminum sulfate was designed to be 1.0 mol% based on 100% by weight of the total metals excluding lithium in the final positive electrode active material. Next, cobalt sulfate was added and mixed for about 10 to 40 minutes. At this time, the nickel content in the cobalt sulfate was designed to be 0.2 mol% based on 100% by weight of the total metals excluding lithium in the final positive electrode active material. After removing the solvent from the mixed solution and drying at 190°C, a second heat treatment was performed at 825°C for 8 hours in an oxygen atmosphere to prepare the final positive electrode active material.

[0123] 2. Manufacturing of lithium secondary batteries 98.5 wt% of the prepared positive electrode active material, 1.0 wt% of polyvinylidene fluoride binder, and 0.5 wt% of carbon nanotube conductive material were mixed to prepare a positive electrode active material layer slurry, which was then coated on an aluminum foil current collector, dried, and rolled to prepare a positive electrode. At this time, the loading level of the positive electrode active material layer was 10 mg / cm. 2 and the density of the final rolled cathode was about 3.4 g / cc.

[0124] A negative electrode active material layer slurry was prepared by mixing 97.5 wt% graphite negative electrode active material, 1.5 wt% carboxymethyl cellulose, and 1 wt% styrene butadiene rubber in an aqueous solvent. The negative electrode active material layer slurry was coated on a copper foil current collector, and then dried and rolled to prepare a negative electrode.

[0125] A polytetrafluoroethylene separator was used, and a lithium secondary battery was fabricated in a conventional manner using an electrolyte solution prepared by dissolving 1M LiPF6 in a solvent mixture of ethylene carbonate and dimethyl carbonate in a volume ratio of 3:7.

[0126] Comparative Example 1 In the manufacture of the positive electrode active material, the Al and Co coating process is not performed, and LiNi 0.75 Mn 0.23 Al 0.02 A positive electrode active material and a lithium secondary battery were produced in substantially the same manner as in Example 1, except that the O2 composite oxide itself was used as the positive electrode active material.

[0127] Comparative Example 2 A positive electrode active material and a lithium secondary battery were manufactured in substantially the same manner as in Example 1, except that in the preparation of the positive electrode active material, Co coating was not performed and only Al was dry coated.

[0128] The Al dry coating method is as follows: 0.75 Mn 0.23 Al 0.02 A composite oxide in the form of secondary particles, which is O2, and aluminum oxide powder were mixed and heat-treated at 825°C for 8 hours in an oxygen atmosphere to obtain a cathode active material coated with Al in a dry manner.

[0129] Comparative Example 3 A positive electrode active material and a lithium secondary battery were manufactured in substantially the same manner as in Example 1, except that in the preparation of the positive electrode active material, Co coating was not performed and only Al was wet coated.

[0130] That is, after aluminum sulfate was mixed with a distilled water solvent, the composite oxide was added and mixed for about 20 to 60 minutes, the solvent was removed, and the mixture was dried at 190°C and subjected to a second heat treatment at 825°C for 8 hours in an oxygen atmosphere to produce a positive electrode active material according to Comparative Example 3.

[0131] Comparative Example 4 A positive electrode active material and a lithium secondary battery were manufactured in substantially the same manner as in Example 1, except that in the preparation of the positive electrode active material, only Co was wet-coated without Al coating.

[0132] That is, the composite oxide was added to a distilled water solvent, and cobalt sulfate was added and mixed for about 10 to 40 minutes. After that, the solvent was removed and the mixture was dried at 190°C. Then, a second heat treatment was performed at 825°C for 8 hours in an oxygen atmosphere to produce the cathode active material according to Comparative Example 4.

[0133] Evaluation example 1: Analysis of positive electrode active material The positive electrode active material particles prepared in Example 1 were cut using a focused ion beam (FIB) device, and the cross section was subjected to SEM-EDS analysis. FIG. 5 is an SEM image of the cross section of the positive electrode active material of Example 1. FIG. 6 is an image in which the Al element is highlighted in FIG. 5 by SEM-EDS analysis, and FIG. 7 is an image in which the Co element is highlighted in FIG. 5 by SEM-EDS analysis. Referring to FIGS. 5 to 7, it can be seen that a first coating layer containing Al was formed on the surface of the secondary particles with a uniform thickness, and a second coating layer containing Co was formed on the first coating layer in the form of a thin and uniform film, so that a double coating layer was formed overall, and a positive electrode active material having a double core-shell structure was prepared.

[0134] Evaluation example 2: Charge / discharge characteristics and high-temperature life characteristics The lithium secondary batteries manufactured in Example 1 and Comparative Examples 1 to 4 were initially charged and discharged at a constant current of 0.2 C to 4.45 V and a constant voltage of 0.05 C at 25° C., and then discharged at 0.2 C to 3.0 V. The initial discharge capacities are shown in Table 1 below.

[0135] Next, a cycle of charging at 1.0 C and discharging at 1.0 C in the voltage range of 3.0 V to 4.45 V at 45° C. was repeated 25 times or more, and the ratio of the 25-cycle discharge capacity to the initial discharge capacity was calculated and shown in Table 1 below as a high-temperature life.

[0136] [Table 1]

[0137] Referring to Table 1, it can be seen that the lithium secondary battery of Example 1 is more excellent in initial discharge capacity and life characteristics than those of Comparative Examples 1 to 4.

[0138] Although the preferred embodiments have been described in detail above, the scope of the present invention is not limited thereto, and various modifications and improvements made by those skilled in the art using the basic concepts defined in the claims also fall within the scope of the present invention. [Explanation of symbols]

[0139] 100 Lithium secondary battery 10 positive electrode 11 Positive electrode lead tab 12 Positive terminal 20 negative electrode 21 Negative electrode lead tab 22 Negative terminal 30 Separator 40 Electrode assembly 50 cases 60 Sealing material 70 Electrode tab 71 Positive electrode tab 72 Negative electrode tab

Claims

1. Core particles containing a layered lithium nickel-manganese composite oxide; a first coating layer located on the surface of the core particle and containing Al; and The positive electrode active material includes a second coating layer located on the first coating layer, the second coating layer including Co.

2. 2. The positive electrode active material according to claim 1, wherein the layered lithium nickel-manganese composite oxide of the core particle has a nickel content of 60 mol% to 80 mol% and a manganese content of 10 mol% or more relative to 100 mol% of all metals excluding lithium.

3. 2. The positive electrode active material according to claim 1, wherein the layered lithium nickel-manganese composite oxide of the core particle further contains aluminum, and the content of aluminum in the core particle is 1 mol % to 3 mol % relative to 100 mol % of all metals excluding lithium.

4. 2. The positive electrode active material according to claim 1, wherein the layered lithium nickel-manganese composite oxide of the core particle has a cobalt content of 0 mol % to 0.01 mol % relative to 100 mol % of all metals excluding lithium.

5. The layered lithium nickel-manganese composite oxide of the core particle is represented by chemical formula 1, and is the positive electrode active material according to claim 1: [Chemical formula 1] Li a1 Ni x1 Mn y1 Al z1 M 1 w1 O 2-b1 X b1 In Chemical Formula 1, 0.9≦a1≦1.8, 0.6≦x1≦0.8, 0.1≦y1≦0.4, 0≦z1≦0.03, 0≦w1≦0.3, 0.9≦x1+y1+z1+w1≦1.1, and 0≦b1≦0.1; M 1 is one or more elements selected from B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y, and Zr, and X is one or more elements selected from F, P, and S.

6. The positive electrode active material according to claim 1 , wherein the first coating layer and the second coating layer are in the form of a continuous film.

7. The thickness of the first coating layer is 5 nm to 40 nm; The positive electrode active material according to claim 1 , wherein the second coating layer has a thickness of 10 nm or less.

8. 2. The positive electrode active material of claim 1, wherein a ratio of a thickness of the second coating layer to a thickness of the first coating layer is less than 0.

5.

9. The Al content of the first coating layer is 0.1 mol % to 2 mol % based on 100 mol % of all metals excluding lithium in the positive electrode active material, 2. The positive electrode active material according to claim 1, wherein the Co content of the second coating layer is 0.01 mol % to 1 mol % based on 100 mol % of all metals in the positive electrode active material excluding lithium.

10. The Al content of the first coating layer is 0.5 mol % to 1.5 mol % based on 100 mol % of all metals excluding lithium in the positive electrode active material, 2. The positive electrode active material according to claim 1, wherein the Co content of the second coating layer is 0.05 mol % to 0.5 mol % based on 100 mol % of all metals in the positive electrode active material excluding lithium.

11. The positive electrode active material according to claim 1 , wherein a ratio of a Co content in the second coating layer to an Al content in the first coating layer is less than 0.

5.

12. the first coating layer comprises aluminum oxide, lithium-aluminum oxide, or a combination thereof; 10. The active cathode material of claim 1, wherein the second coating layer comprises cobalt oxide, lithium-cobalt oxide, aluminum-cobalt oxide, lithium-aluminum-cobalt oxide, or a combination thereof.

13. The positive electrode active material according to claim 1 , wherein the first coating layer and the second coating layer have a layered structure.

14. The core particle is in the form of a secondary particle formed by agglomeration of a plurality of primary particles, The positive electrode active material of claim 1 , further comprising a grain boundary coating portion containing Al and located on a surface of a primary particle inside the secondary particle.

15. The positive electrode active material according to claim 14 , wherein an Al content in the grain boundary coating portion is less than an Al content in the first coating layer.

16. The average particle size (D 50 2. The positive electrode active material according to claim 1, wherein the thickness of the first electrode is 10 μm to 20 μm.

17. A layered nickel-manganese composite hydroxide and a lithium raw material are mixed and subjected to a first heat treatment to obtain a layered lithium nickel-manganese composite oxide; An Al raw material is added to an aqueous solvent, the lithium nickel-manganese composite oxide is added and mixed, and then a Co raw material is added and mixed; and drying the resultant mixture and subjecting it to a second heat treatment.

18. The method for producing a positive electrode active material according to claim 17, wherein, in the layered nickel-manganese composite hydroxide, the nickel content is 60 mol% to 80 mol%, the manganese content is 10 mol% or more, the aluminum content is 0 mol% to 3 mol%, and the cobalt content is 0 mol% to 0.01 mol%, relative to 100 mol% of the total metals.

19. The Al content in the Al raw material is 0.1 mol % to 2 mol % relative to 100 mol % of all metals excluding lithium in the positive electrode active material, The method for producing a positive electrode active material according to claim 17, wherein the Co content in the Co raw material is 0.01 mol % to 1 mol % relative to 100 mol % of all metals excluding lithium in the positive electrode active material.

20. The Al source includes aluminum nitrate, aluminum sulfate, aluminum carbonate, aluminum hydroxide, or a combination thereof; 18. The method of claim 17, wherein the Co raw material comprises cobalt nitrate, cobalt sulfate, cobalt carbonate, cobalt hydroxide, or a combination thereof.

21. The method for producing a positive electrode active material according to claim 17, wherein the solution in which the Al raw material is added to the aqueous solvent has a pH of 1.5 to 3.

5.

22. The first heat treatment is carried out at 750°C to 950°C, The method for producing a positive electrode active material according to claim 17, wherein the second heat treatment is performed at 700°C to 850°C.

23. A positive electrode current collector, and a positive electrode active material layer located on the positive electrode current collector, The positive electrode active material layer comprises the positive electrode active material according to any one of claims 1 to 16.

24. The loading level of the positive electrode active material layer is 10 mg / cm 2 ~40mg / cm 2 24. The positive electrode of claim 23,

25. 24. The positive electrode of claim 23, wherein the positive electrode active material layer has a density of 3.3 g / cc to 3.7 g / cc.

26. The positive electrode according to claim 23 . a negative electrode, and A lithium secondary battery comprising an electrolyte.

27. 27. The lithium secondary battery according to claim 26, having a charging voltage of 4.45 V or higher.

Citation Information

Patent Citations

  • Positive electrode material and preparation method thereof, secondary battery and electric equipment

    CN115842117A

  • Li-ni composite oxide particle powder for nonaqueous electrolyte secondary battery, its manufacturing method, and nonaqueous electrolyte secondary battery

    JP2008251532A